Self-expandable metal stent of esophagogastric junction versus pyloric area obstruction in advanced gastric cancer patients: Retrospective, comparative, single-center study. Issue 33 (14th August 2020) - Kim, Deok Yeong; Moon, Hee Seok; Kwon, In Sun; Park, Jae Ho; Kim, Ju Seok; Kang, Sun Hyung; Lee, Eaum Seok; Kim, Seok Hyun; Lee, Byung Seok; Sung, Jae Kyu; Jeong, Hyun Yong
Abstract : Abstract: Upper gastrointestinal stenting is a palliative treatment for relieving symptoms such as nausea, vomiting, and dietary intake in patients with obstruction due to inoperable advanced stomach cancer. Self-expandable metal stent (SEMS) implantation for malignant obstruction has recently become more effective, safer, and less expensive than operative modality. It also has better short-term outcomes, particularly a shorter hospital stay and a more rapid return to oral intake, than surgical treatment. However, there is no comparative analysis regarding the efficacy, side effects, and survival rate of stenting between the esophagogastric junction (EGJ) and pyloric obstructions. To compare the prognoses and complications after SEMS implantation between EGJ and pyloric obstructions in advanced gastric cancer. Among advanced gastric cancer patients with gastrointestinal obstruction diagnosed from January 2008 to December 2017 at the Gastroenterology Department of Chungnam National University Hospital, 42 and 76 patients presented with EGJ (EGJ obstruction group) and gastric pyloric obstructions (pyloric obstruction group), respectively. We retrospectively reviewed the survival period, changes in food intake, and complications of these patients before and after SEMS placement. The prevalences of aspiration pneumonia were 11.9% (5/42) and 2.6% (2/76) in the EGJ and pyloric obstruction groups, respectively, before SEMS placement ( P value: .041). Other symptoms associated with gastric malignant obstruction were not statistically different between the groups. Success rate and adverse events did not significantly differ between the EGJ and pyloric obstruction groups. There was no difference in frequency of stent reinsertion procedures performed owing to reobstruction, but the reprocedure average period was statistically significantly longer in the EGJ obstruction group [EGJ obstruction: 158.3 days (±42.4); pyloric obstruction: 86.0 days (±29.1)] ( P value: .022). As an index of improved dietary status, the Gastric Outlet Obstruction Scoring System score was not significantly different between the groups before and after SEMS placement. The EGJ and pyloric obstruction groups did not significantly differ in prognosis or complication rates. However, EGJ stent was more stable than pyloric stent when reobstruction was considered.